الجسد الذكوري في رواية " عازب حي المرجان " لربيعة جلطي أنموذجا - بوشلالق, عبد العزيز; نور الهدى, العيفة (Université de M'sila, 2020)
ملخص: إن انطلاق الروائية في كتاباتها على تيمة الجسد الذكوري هو أمر يثير الدهشة عند البعض باعتبار ذلك طابوها يمنع منعا باتا الحديث عنه ،ليتحول الجسد في الإبداع الروائي إلى لغة معبرة ومشفرة ،تحمل في ثناياها رسائل مختلفة تبثها للمتلقي، ومعه يتحول الكائن الورقي في الرواية /الجسد الورقي إلى كائن موجود متخيل بفعل القراءة ،وعليه كان اشتغال الروائية الجزائرية "ربيعة جلطي"في عملها الروائي "عازب حي المرجان على الجسد الذكوري معطية إياه بعدا فلسفيا ونفسيا كجدلية تحمل الكثير من المتناقضات.، ولذلك وجب علينا التساؤل: كيف صوّرت الكاتبة الجسد الذّكوري في هذه الرّواية ؟ Abstract: The novel's launch in its writings on the masculine body is surprising to some as it is forbidden to talk about it, so that the body in the novel creativity turns into expressiveand encrypted language, carrying in its folds different messages transmitted to the recipient, and with it turns the paper object in the novel /paper body To an existing being imagined by reading, and therefore the work of the Algerian novelist Rabia Galti in her novel work " The bachelor of the coral neighborhood on the male body giving it a philosophical and psychological dimension as a dialectic carrying many contradictions, so we had to wonder: how did the writer portray t
Keywords: الرواية، الجسد الذكوري ربيعة جلطي. The novel . the masculine body . Rabia Galti